2014
DOI: 10.1111/cpf.12144
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive effects and performance responses between different resistance training intensities and exercise orders in apparently health women

Abstract: To compare the hypotensive effect and performance responses between different resistance training intensities and different exercise orders in apparently healthy women, thirteen apparently healthy women performed four resistance training sessions in randomized order. One group performed the resistance training exercises with 60% of 1RM (SeqA60%): leg press (LG), chest press (CP), leg extension (LE), lat pull down (PD), leg curl (LC) and biceps curl (BC). Another group performed the resistance training exercise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
2
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 31 publications
0
34
2
6
Order By: Relevance
“…Previous studies 5,6,10 , suggest that several mechanisms can influence the cardiovascular and PHE behavior. So, overall the hypotensive effect may be associated with factors such as occlusion of the vessels and arteries, cardiac output, stroke volume, autonomic modulation of heart rate through the sympathetic and parasympathetic nerves, in addition to peripheral vascular resistance that can be changed during training [30][31][32] .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Previous studies 5,6,10 , suggest that several mechanisms can influence the cardiovascular and PHE behavior. So, overall the hypotensive effect may be associated with factors such as occlusion of the vessels and arteries, cardiac output, stroke volume, autonomic modulation of heart rate through the sympathetic and parasympathetic nerves, in addition to peripheral vascular resistance that can be changed during training [30][31][32] .…”
Section: Discussionmentioning
confidence: 93%
“…In relationship to training volume, previous studies [22][23][24][25] does not found effect on PHE magnitude after its modification. In 2015 Cavalcante et al 5 demonstrated that PHE occur independently of exercise intensity without expressed cardiovascular overload during the session, however, there are few study 5,[10][11][12] on literature evaluating different manipulation of volume and intensity on RE and the magnitude of PEH. In this study the PHE were found after 60 min and 24 hour after PWL exercise session just in SBP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have evaluated hypotensive responses after RE sessions held at different intensities (Bentes et al, 2015;Matos et al, 2013;Mohebbi, Rahmaninia, Vatani, & Faraji, 2009;O'Connor, Bryant, Veltri, & Gebhardt, 1993;Polito, Simão, Senna, & Farinatti, 2003;Simão, Fleck, Polito, Monteiro, & Farinatti, 2005). Studies by Simão, Fleck, Polito, Monteiro, and Farinatti (2005) and Polito, Simão, Senna, and Farinatti (2003) suggest that RE sessions with high intensities (100% of 6RM to failure) are more effective than moderate intensity programs (12 repetitions with 50% of 6RM) resulting in a longer duration PEH in trained subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional resistance exercises (REs) have been used to promote post exercise hypotension, which occurs as a result of the reduced vascular resistance observed in these exercise protocols [1][2][3] . The reduced vascular resistance is caused by an increase in the endothelial substances and by reductions in the sympathetic nervous system activity and cardiac output 4 .…”
Section: Introductionmentioning
confidence: 99%